Lecturas - (:unkn) unknown (My University)
Fleitas, Emiliano. Cuevas, Cristian. González, John Balbuena. Fernández, Maximiliano. Ríos, Lidia. Bustamante, Martín. Prieto, Silvina. Bustelo, Cynthia.
Keywords: Escritura; Cárceles; Letras en situación de encierro